The Impact of Oxytocin Massage and Banana Flower Consumption (Musa balbisiana colla) on the Prolactin Level in Breastfeeding Mothers - Nurmiaty, Nurmiaty; Aisa, Sitti; Aswita, Aswita; Dolufu, Muliati; Rahman, Nur; Batbual, Bringiwatty (JURNAL INFO KESEHATAN, 2023)
For a long time, banana flowers have been believed to increase breast milk production. Thus, many people consume them as vegetables for breastfeeding mothers. This research examines the impact of oxytocin massage and banana flower consumption on prolactin levels in breastfeeding mothers. The method used a true experiment control group design in which samples were divided into three groups: Group 1 was treated with oxytocin massage, group 2 was treated with banana flower consumption, and Group 3 was given intervention with oxytocin massage and banana flower consumption. The massage was conducted every day for 5-10 minutes. The banana flower vegetable was served as much as 150 grams daily. The first blood sampling was done pre-intervention on the third day of postpartum. The second blood sampling was done after intervention on the tenth postpartum day following the intervention. The checkup of prolactin level was through Chemiluminescent Microparticle Immunoassay (CMIA). This research utilized a T-test exam to analyze the data. The average difference in prolactin levels in pre-and-post intervention in group 1 was -61,75 ng/mL. Although decreasing prolactin levels occurred, there was no significant interval between pretest and post-test. The difference in prolactin levels in pre-and-post intervention in group 2 was 103,61 ng/mL. The prolactin level increased but not significantly. In group 3, the difference levels were about 110,22 ng/mL. In this group, a significant prolactin level increase had occurred. The conclusion is that the combination of banana flower and oxytocin massage evolved the prolactin level in nursing mothers. Research related to enforcing the recommendation of breastfeeding mothers to consume traditional galactagogues.